THE ROLE AND IMPORTANCE OF BASIC LAWS AND REGULATORY ACTS IN THE MANAGEMENT OF EMERGENCY SITUATIONS AND POPULATION SECURITY (American Journal of Pedagogical and Educational Research, 2023)
The article analyzes scientific studies with various aspects of the topic of law enforcement in emergency situations. It has been determined that ensuring the rule of law in emergency situations includes the timely adoption of required and fair regulatory legal acts.